2001
DOI: 10.1002/hed.1035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thyroid nodules with technetium‐99m MIBI and technetium‐99m pertechnetate

Abstract: In combination with FNA and three-phase pertechnetate scan, MIBI could be helpful in preoperative assessment of thyroid nodules. Intense MIBI activity increases the probability of thyroid cancer, whereas reduced activity drastically decreases the probability of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
5
33
0
8
Order By: Relevance
“…Since first reported in 1987, 99m Tc-MIBI imaging has been increasingly used in the diagnosis of thyroid cancer due to its low radiation exposure and convenience of use (Sathekge et al, 2001). However, the reported performances of 99m Tc-MIBI imaging in the diagnosis of thyroid cancer were conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since first reported in 1987, 99m Tc-MIBI imaging has been increasingly used in the diagnosis of thyroid cancer due to its low radiation exposure and convenience of use (Sathekge et al, 2001). However, the reported performances of 99m Tc-MIBI imaging in the diagnosis of thyroid cancer were conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specificity of such exam is low, therefore the use of radioisotope imaging has significantly declined (Marc, 2008). To further improve the accuracy, some researchers tried to combine the imaging of thyroid pro-tumor and thyroid gland to differentiate the benign and malignant thyroid nodules (Sathekge et al, 2001), which were unfortunately shown to be ineffective and only had very limited clinical value. The aim of this study is to use the combined quantitative analysis of both thyroid blood flow imaging and static imaging data to differentiate benign and malignant thyroid nodules, which may provide valuable information for the determination of treatment plan, surgical approach and prognosis.…”
Section: Quantitative Analysis Of Thyroid Blood Flow and Static Imagimentioning
confidence: 99%
“…Since "cold nodules" do not show any uptake of 99 m Tc-pertechnetate, 99 m Tc-MIBI has to be used as an alternative tracer to provide a comparison of uptake in "cold" nodules prior to and after microwave ablation. Previous studies have demonstrated the high potential of MIBI in detecting malignant thyroid nodules with high sensitivity, especially when combined with fine-needle aspiration cytology [24]. However, the uptake of 99 m Tc-MIBI is not only present in nodules of suspected malignancy, but also in benign cold nodules.…”
mentioning
confidence: 99%
“…MIBI was first described in the 1980s [1,2]. Originally developed for myocardial perfusion scintigraphy for the detection and localization of coronary artery disease, it went on to eventually achieve registration not only for this indication, but also for the assessment of global ventricular function, scintimammography for the detection of suspected breast cancer when mammography is equivocal, inadequate or indeterminate, and localization of hyperfunctioning parathyroid tissue in patients with recurrent or persistent hyperparathyroidism, both primary and secondary, and in patients with primary hyperparathyroidism scheduled to undergo initial surgery of the parathyroid glands [3].However, for many years it has been known that MIBI scintigraphy can also be used in the diagnostic work-up of scintigraphically cold and therefore suspicious thyroid nodules in combination with fine needle biopsy (FNB) [4][5][6][7][8][9][10][11][12] Tc-pertechnetate thyroid scintigraphy MIBI scintigraphy can achieve a very high negative predictive value ranging from 88 % to 100 % with a mean of 97 %. Furthermore, the sensitivity of MIBI scintigraphy is similarly good with an aggregate value of 96 %.…”
mentioning
confidence: 99%
“…However, for many years it has been known that MIBI scintigraphy can also be used in the diagnostic work-up of scintigraphically cold and therefore suspicious thyroid nodules in combination with fine needle biopsy (FNB) [4][5][6][7][8][9][10][11][12] Tc-pertechnetate thyroid scintigraphy MIBI scintigraphy can achieve a very high negative predictive value ranging from 88 % to 100 % with a mean of 97 %. Furthermore, the sensitivity of MIBI scintigraphy is similarly good with an aggregate value of 96 %.…”
mentioning
confidence: 99%